The housing question tensions, continuities, and contingencies in the modern city - Murphy, Edward 1971-; Hourani, Najib B. (Farnham, Surrey, England Ashgate, 2013)
Drawing on cutting edge perspectives from urban studies, this book grants renewed, interdisciplinary energy to the housing question. It explores how housing raises a series of vexing issues surrounding rights, identity, and justice in the modern city. Through finely detailed studies that illuminate national and international particularities-ranging from analyses of urban planning in the Soviet Union, the post-Katrina reconstruction of New Orleans, to squatting in contemporary Lima - the volume underscores how housing questions matter in a wide range of contexts.
List of figures -- Notes on contributors -- Acknowledgments -- Introduction: housing questions past, present, and future -- Part I. Putting high modernist planning in its place -- 1. Modernity unbound : tol'iatti as the new soviet city par exellence -- 2. The transnationalization of the "housing problem": social sciences and developmentalism in postwar Argentina -- 3. Infrastructural thinking : urban housing in former Czechoslovakia from the Stalin era to EU accession -- 4. The politics of public and private space : housing and urbanism in divided Berlin -- Part II. The state of uneven geographic developments -- 5. The housing question of disaster reconstruction : rebuilding New Orleans on the tenants of an ownership society -- 6. Public transit planning and austerity in neoliberal Chicago -- 7. Reinventing favela aesthetics: from shacks to public housing buildings -- 8. Privatization, marketization, and the homeownership paradox: the housing predicaments of China's urban poor -- Part III. Spaces of home in the city of rights -- 9. Recognizing (dis)order: topographies of power and property in Lima's periphery -- 10. Between housing and home : property titling and the dilemmas of citizenship in Santiago, Chile -- 11. citizenship and the urban polity : right to the city and the meanings of home -- Part IV. Final reflections -- 12. Assemblage and structure : toward new urban political economies -- 13. Housing crises, right to the city, and citizenship -- Bibliography -- Index.
Includes bibliographical references (pages 271-304) and index.
Keywords: Housing policy -- Case studies